BIOSECURITY PRACTICES ON LAYER FARMS IN JATILUWIH VILLAGE, TABANAN, BALI - Gabriel Adam Salombe; I Wayan Masa Tenaya; I Wayan Sudira; Romy Muhammad Dary Mufa (Fakultas Kedokteran Hewan Universitas Udayana, 2025)
The layer poultry industry plays a vital role in fulfilling the population's demand for animal protein. To support sustainable livestock production, farms must implement biosecurity as a proactive strategy to prevent disease spread, thus ensuring the production of healthy and consumable animal-derived food products. This study aimed to evaluate the level of knowledge and implementation of biosecurity practices, including isolation, traffic control, and sanitation, and to analyze the correlation between knowledge and biosecurity implementation in layer poultry farms in Jatiluwih Village, Penebel District, Tabanan Regency, Bali. Data were collected through interviews using a total sampling method with a structured questionnaire based on the Guttman scale as the research instrument. The data were then tabulated using Microsoft Excel and analyzed with descriptive and quantitative methods. Spearman's rank correlation test was used to analyze the relationship between knowledge and biosecurity implementation. The results showed that the average knowledge of farmers regarding biosecurity was good (54.5%), with moderate implementation of isolation (48.1%), low implementation of traffic control (28.8%), and good sanitation practices (65.2%). However, the correlation between knowledge and the implementation of biosecurity practices was not statistically significant (p>0.05). Based on these findings, it can be concluded that although there was a positive correlation between knowledge and biosecurity implementation, this relationship was very weak between knowledge and traffic control, and moderate between knowledge and isolation, and knowledge and sanitation. Therefore, a more practical and adaptive approach is needed so that farmers can effectively and consistently implement the biosecurity concepts they understand.